Seasonal variability in Third World agriculture: the consequences for food security - Sahn, David E. (International Food Policy Research Institute, 1989)
The purpose of this book is to explore the seasonality of household food security. This involves examining the extent, patterns, causes, and consequences of seasonal variations in wages, agricultural earnings, food availability, prices, consumption, and nutritional status. In addition, we are interested in whether seasonal cycles are stable and predictable from years to year, whether and why seasonal fluctuations changes with agricultural and economic development, and the implications of such changes for household food security